Identification of Iron Metabolism-Related Gene Signatures for Predicting the Prognosis of Patients With Sarcomas - Li, Jianyi; Hu, Chuan; Du, Yukun; Tang, Xiaojie; Shao, Cheng; Xu, Tongshuai; Zhao, Zheng; Hu, Huiqiang; Sheng, Yingyi; Guo, Jianwei; Xi, Yongming (Frontiers in Oncology, 2021)
Iron is one of the essential trace elements in the human body. An increasing amount of evidence indicates that the imbalance of iron metabolism is related to the occurrence and development of cancer. Here, we obtained the gene expression and clinical data of sarcoma patients from TCGA and the GEO database. The prognostic value of iron metabolism-related genes (IMRGs) in patients with sarcoma and the relationship between these genes and the immune microenvironment were studied by comprehensive bioinformatics analyses. Two signatures based on IMRGs were generated for the overall survival (OS) and disease-free survival (DFS) of sarcoma patients. At 3, 5 and 7 years, the areas under the curve (AUCs) of the OS signature were 0.708, 0.713 and 0.688, respectively. The AUCs of the DFS signature at 3, 5 and 7 years were 0.717, 0.689 and 0.702, respectively. Kaplan-Meier survival analysis indicated that the prognosis of high-risk patients was worse than that of low-risk patients. In addition, immunological analysis showed that there were different patterns of immune cell infiltration among patients in different clusters. Finally, we constructed two nomograms that can be used to predict the OS and DFS of sarcoma patients. The C-index was 0.766 (95% CI: 0.697-0.835) and 0.763 (95% CI: 0.706-0.820) for the OS and DFS nomograms, respectively. Both the ROC curves and the calibration plots showed that the two nomograms have good predictive performance. In summary, we constructed two IMRG-based prognostic models that can effectively predict the OS and DFS of sarcoma patients.